India as an ambivalent partner in global digital policy: Potenial and limits of cooperation in the digital economy and internet governance - Daniel Voelsen; Christian Wagner (Stiftung Wissenschaft und Politik (SWP), 2022)
Cooperation in global digital policy is considered one of the most promising fields in the strategic partnership between India and the European Union (EU). However, profound differences are apparent in terms of implementation, for example with regard to data protection, competences of security authorities and the future global digital order. Meanwhile, similar problems are being addressed in the EU's negotiations with the US on digital trade issues. Possible compromises there could also form components of an understanding with India. Shared democratic values are consistently referred to as a justification for efforts to strengthen Europe's cooperation with India. In their Roadmap 2025, India and the EU affirm their interest in promoting an 'open, free, stable and secure cyber-space' and fighting cybercrime. But the road to this goal is proving to be rocky.
Keywords: 320